STUDY OF INTER-SUBJECT RELATIONS IN BIOLOGY BASED ON WOLTER’S MODEL - Mengliev Islam Abdumuratovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article, based on Voltaire’s model, explores intersubject connections in biology with subjects related to information technology. For this purpose, the “model-algorithm-program” triad is applied and the dynamics of population change over time is studied.